160 The Effect of Frailty and COVID-19 Infection on Clinical Outcomes in Older Adults—A Single Centre Retrospective Study. (16th March 2021) - Okuwoga, O; Mufti, S
Abstract: Introduction: It was anticipated that the COVID-19 pandemic would put a strain on our healthcare system, disproportionately affecting older people. NICE guidance recommended using frailty scoring to support decision making around escalation of care. This study aimed to assess frailty, demographics and COVID-19 infection and to investigate how these related to outcomes of patients aged over 65 years admitted to hospital. Methods: A single centre retrospective cohort study was carried out by reviewing the electronic health records of all admissions over 65 years. Data points collected included length of stay (LOS), frailty score using the Rockwood Clinical Frailty Scale (CFS) and mortality. Patients were stratified into COVID and non-COVID based on health records and into non-frail (CFS 1–4) and frail (CFS 5–9). Results: A total of 257 patients admitted between 30th March and 30th April 2020 were included in the study (mean age 79 years, 43% female). 141 (54.9%) of patients were diagnosed with COVID-19 infection. 120 patients had CFS 1–4 and 136 has CFS 5–9. 1 patient did not have a frailty score due to insufficient information. 68 (26.8%) of all patients died during the admission. The relative risk (RR) of mortality of patients with coronavirus was 6.3 (95% CI 3.1–12.6, p < 0.0001). The RR of mortality for frail patients compared to the non-frail was 2.1 (95% CI 1.3–3.2, p = 0.002). The median LOS for patients with COVID-19 was 5 days, compared to 4 days for patients who did not have coronavirus. Frailty did not predict longer admission, with median LOS of 5 days for both non-frail and frail patients. Conclusion: The results demonstrated in this study show that COVID-19 infection and frailty were significantly associated with increased mortality in older patients. This validates the continued use of frailty scoring of older patients on admission to support care planning.